2016
DOI: 10.1111/josh.12357
|View full text |Cite
|
Sign up to set email alerts
|

Individual and School‐Level Socioeconomic Gradients in Physical Activity in Australian Schoolchildren

Abstract: School-built, policy, and resource environments are similar across different SES-level schools. Therefore, some other mechanism must be underlying the SES gradients seen in MVPA participation in Australian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
2
14
1
Order By: Relevance
“…Similarly, we found potential barriers to enhancing children's PA; skill development and fitness in school were more prevalent in low SES schools than high SES schools and most barriers were associated with curriculum and teaching, and school policy and environment. Our findings reinforce the importance of assessing not only the physical features of the school, as has been done in a previous Australian study, but also the wider psychosocial characteristics—school leadership, wider school environment, and ethos surrounding PA and teacher behaviors…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, we found potential barriers to enhancing children's PA; skill development and fitness in school were more prevalent in low SES schools than high SES schools and most barriers were associated with curriculum and teaching, and school policy and environment. Our findings reinforce the importance of assessing not only the physical features of the school, as has been done in a previous Australian study, but also the wider psychosocial characteristics—school leadership, wider school environment, and ethos surrounding PA and teacher behaviors…”
Section: Discussionsupporting
confidence: 88%
“…The distinction between school‐ and individual‐level SES may be an important factor in the delivery of school‐based PA interventions within schools. Evidence from the United States suggests that school‐level SES does influence children's PA, with additional support from an Australian study . The Australian study also found a clear association between SES and in‐school PA, with school facilities, sports, and policies promoting PA not differing significantly among schools of different SES.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…While this sex‐based disparity in physical activity among youth is not new, recent findings have suggested that influences on physical activity from the school environment may be weaker on girls compared to boys . In addition, previous studies have found weaker effects of school‐based physical activity programs in low SES schools compared to higher SES schools . Our results indicate that “ Health Empowers You!…”
Section: Discussioncontrasting
confidence: 45%
“…Schools are better able to enhance children’s PA when they emphasise resource provision for PA within the school day, create a ‘‘culture’’ of PA, train teachers to support a positive climate for PA promotion, and ensure extracurricular PA opportunities for all children [ 17 , 19 ]. When the school day is targeted and whole school approaches are adopted, opportunities for all can be positively impacted [ 66 , 67 , 68 ]. Health promoting school initiatives have operated in NI in the past and could provide a framework for change to help tackle some of the issues presented.…”
Section: Discussionmentioning
confidence: 99%